Analisis Perbandingan Kandungan Protein Berbasis Hewani Menggunakan Metode Biuret - Mirwa Adiprahara Anggarani; Yurita Gita Puspa Nugrainglahi; Maretha Nur Rohma; Adinda Debita Prihastina; Soesilowati Soesilowati (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2026)
Monitoring and evaluating students' analytical rigor in the biochemistry laboratory is crucial for fostering higher-order thinking skills. However, systematic assessment of their error analysis abilities is rare. This study aimed to evaluate undergraduate students' laboratory competencies using a cross-sectional comparative research design focused on protein quantification. Eleven different animal-based food ingredients across four groups (meat, local freshwater fish, poultry eggs, and seafood) were analyzed in three biological replicates (total n = 33 experimental units). The core methodology was colorimetric quantification using the Biuret method via UV-Vis spectrophotometry at 540 nm. The resulting experimental data showed that the meat group yielded the highest extractable protein content (6.48 ± 0.45%), followed by local freshwater fish (5.02 ± 0.31%), poultry eggs (4.98 ± 0.28%), and seafood (2.42 ± 0.19%). The obtained protein content data were then statistically analyzed using the non-parametric Kruskal-Wallis test to determine whether there was a significant difference in protein values between the four groups (p = 0.124, η² = 0.15, indicating a small to medium effect size). Major limitations of this practical protocol were identified, including that the simple extraction method selectively isolates only the water-soluble fraction of sarcoplasmic proteins. This leads to systematic underestimation (up to 80-90% deviation) when compared to theoretical total protein literature standards. Methodologically, this study highlights the limitations of standard university extraction protocols. Pedagogically, these data reveal problematic facts that could form the basis for curriculum changes and recommendations for providing better diagnostic tools.